Polarization Behaviour of Stainless Steel Type 302 in HCl Solution of Benzotriazole - HOSSEINI, S.M.A.; EFTEKHAR, S.; AMIRI, M. (Asian Journal of Chemistry, 2010)
The inhibition behaviour of stainless steel type 302 in different concentrations (1 × 10-3 to 8 ×10-3 M) of benzotriazole (BTA) in 1 M HCl at various temperatures (10, 30, 50 ± 1ºC) has been studied potentiodynamically. The open circuit potential (OCP) values noted were negative before polarization but after completion of the experiment they turned positive and remained stable over long period of time indicating formation of passive and protective film on the surface of sample. It is observed that cathodic current density values increase with increasing cathodic potential (more negative). It is found that corrosion potential (Ecorr) and passive potential (Ep) increase (toward + ve potential) with increasing benzotriazole concentrations, while corrosion current density (icorr), critical current density (icr), passive current density (ip) and corrosion rate decrease. Micrographs taken from the surface of the exposed samples in the blank solution and solution containing benzotriazole clearly reveals inhibiting role of this compound.